PENGEMBANGAN APLIKASI MARBEL SEBAGAI MEDIA PEMBELAJARAN PAI UNTUK MENINGKATKAN KETAKWAAN SISWA KELAS V SD - Fahmi Pradana; Nunung Nurhayati; Puput Agisni Salimah; Ani Nur Aeni (Universitas Sarjanawiyata Tamansiswa, 2022)
The use of applications is very helpful for teachers to create a conducive learning climate. Therefore, this study aims to determine the extent of the usefulness of the MarBel application that the researchers have made in increasing the piety of students, especially in the subject of Islamic Religious Education. The research method used in this research is descriptive quantitative. The subjects of this study were students and teachers of class V Elementary School at SDN Pasir Jati. The results of the study show that the MarBel application is very helpful for students in improving the quality of piety, helps make it easier to understand the material in Islamic Religious Education subjects about piety, and equips students in operating the application. The MarBel application is also designed to make it easier for teachers to deliver material to students to make it more practical and efficient. The MarBel application is designed for researchers not only in terms of appearance and style but this application has been adapted to the content and curriculum of Islamic Religious Education subjects in Elementary Schools. The language used is very light, so students can easily operate the MarBel application.